Calcium/calmodulin‐dependent protein kinase regulates the PINK1/Parkin and DJ‐1 pathways of mitophagy during sepsis. Issue 10 (19th September 2017) - Zhang, Xianghong; Yuan, Du; Sun, Qian; Xu, Li; Lee, Emma; Lewis, Anthony J.; Zuckerbraun, Brian S.; Rosengart, Matthew R.
ABSTRACT: During sepsis and shock states, mitochondrial dysfunction occurs. Consequently, adaptive mechanisms, such as fission, fusion, and mitophagy, are induced to eliminate damaged portions or entire dysfunctional mitochondria. The regulatory PINK1/Parkin and DJ‐1 pathways are strongly induced by mitochondrial depolarization, although a direct link between loss of mitochondrial membrane potential (ΔΨ ) and mitophagy has not been identified. Mitochondria also buffer Ca 2+, and their buffering capacity is dependent on ΔΨ . Here, we characterize a role for calcium/calmodulin‐dependent protein kinase (CaMK) I in the regulation of these mechanisms. Loss of ΔΨ with either pharmacologic depolarization or LPS leads to Ca 2+ ‐dependent mitochondrial recruitment and activation of CaMKI that precedes the colocalization of PINK1/Parkin and DJ‐1. CaMKI is required and serves as both a PINK1 and Parkin kinase. The mechanisms operate in both immune and nonimmune cells and are induced in in vivo models of endotoxemia, sepsis, and hemorrhagic shock. These data support the idea that CaMKI links mitochondrial stress with the PINK1/Parkin and DJ‐1 mechanisms of mitophagy.—Zhang, X., Yuan, D., Sun, Q., Xu, L., Lee, E., Lewis, A. J., Zuckerbraun, B. S., Rosengart, M. R. Calcium/calmodulin‐dependent protein kinase regulates the PINK1/Parkin and DJ‐1 pathways of mitophagy during sepsis. FASEB J. 31, 4382‐4395 (2017). www.fasebj.org